Working-class Hollywood : silent film and the shaping of class in America - Ross, Steven J., 1949- (Princeton University Press, 1998)
This pathbreaking book reveals how Hollywood became "Hollywood" and what that meant for the politics of America and American film. Working-Class Hollywood tells the story of filmmaking in the first three decades of the twentieth century, a time when going to the movies could transform lives and when the cinema was a battleground for control of the American consciousness. Steven Ross documents the rise of a working-class film movement that challenged the dominant political ideas of the day. Between 1907 and 1930, worker filmmakers repeatedly clashed with censors, movie industry leaders, and federal agencies over the kinds of images and subjects audiences would be allowed to see.